Dread : Poems - Ai, 1947-2010 (New York W.W. Norton, 2003)
Called "one of the most singular voices of her generation" by the New York Times Book Review, Ai is America's foremost poet of the dramatic monologue. In this new collection, she adopts the anguished voices of adults remembering traumatic events from their childhoods -- terrorism, war, sexual abuse, parental violence. These searing poems travel from the horrific flight of a World War II pilot to the World Trade Center attack, from the death of JFK Jr. to the poet's own bastard birth, as Ai delves deeply into the wounded psyches of her characters in their attempt to reach some kind of reconciliation with what is, ultimately, beyond reconciliation. Dread is a collection of ferocious bravery, conjuring purity as a distant memory and the knowledge of evil as an "infinite dark night."